THE INFLUENCE OF NURSE-LED INTERVENTIONS ON PATIENT OUTCOMES: REVIEW - ‏ Jabril Abdulrahman Alzubaidi, Ashwaq Mohammed Alsulobi, Khadijah Ibrahim Alasiri, Anas Abdulwasi Attar, Hani Suleiman Al-Mutairy, Sultan Hadder Alkhatheeri, Mazen Ali Alfaqeeh, Eissa Hamdan Alharbi, Mohammed Abdulrahman Alzubaidi, ,; Hatim Khalofah Alasmari, Saeed Yahya Alqahtani, Mousa Awwadh Alzebali, Sari Hamad Alyhyawi, Abdul Rahman Assaf Al Ghamdi, Bandar Mohammed Hawsawi, Amnah Arar Al Gobi, (Chelonian Research Foundation, 2022)
Nurse-led virtual clinics include a nurse reaching out to a patient for the purpose of clinical consultation, guidance, and treatment planning. This invention has great potential but has not been completely used in health care delivery methods. Although virtual clinics are becoming more popular, there is still a lack of comprehensive knowledge of the complete integration of this platform into everyday nursing practice in the future. This integrative review sought to investigate the use of nurse-led virtual clinic follow-up in chronic care services, with a specific focus on its clinical value and clinical outcomes. A comprehensive literature search was conducted using several online databases, including Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medline, PubMed, Science Direct, Ovid, Scopus, and Google Scholar. Included were publications produced in English that focused on nurse-led virtual clinics for chronic or long-term diseases. Initially, a total of 43 publications published between 2000 and 2015 were identified. A total of twelve papers met the specified criteria for inclusion and were chosen for evaluation. The analysis revealed three primary themes: the technological components of nurse-led virtual clinics, the results of nurse-led virtual clinics, and the potential future implementation of nurse-led virtual clinics in the healthcare sector. Studies have shown that nurse-led virtual clinics prioritize the needs of patients, are cost-effective, and offer treatment efficiently. Nurse-led virtual clinics have promise in efficiently addressing the growing demands and strains healthcare sector. Keywords: nurse-led virtual clinics, integrated review, nurse-led follow-up.